Ivo Goldstein, Jasenovac (Zaprešić; Jasenovac: Fraktura; Javna ustanova Spomen-područje Jasenovac, 2018) 958 str., [32 str.] s tablama : ilustr., zemljop. karte ; 24 cm (Časopis za suvremenu povijest, 2020)
Prikaz knjige